Increasing Teacher Professionalism In The Learning Leadership Process - Rahmadita, Annisa; Bafadal, Ibrahim; Imron, Ali; Arifin, Imron (Universitas Negeri Malang, 2024)
This research was carried out to find out in depth the learning leadership characteristics of the Principal of SMAN 2 Malang in increasing teacher professionalism, strategies for increasing teacher professionalism carried out by the Principal of SMAN 2 Malang as a learning leader, and the results of implementing activities to increase teacher professionalism carried out by the Principal of SMAN 2 Malang as a learning leader. This research uses qualitative research methods with a case study type. The conclusion of this research is that the learning leadership characteristics of the Principal of SMAN 2 Malang in increasing teacher professionalism are demonstrated by a caring attitude towards the school community and participating in learning management. The strategy to increase teacher professionalism carried out by the Principal of SMAN 2 Malang as a learning leader includes holding monthly evaluations to increase teacher professionalism, workshop increasing teacher professionalism, supervision, MGMP, benchmarking to increase teacher professionalism, as well as seminars and dissemination to increase teacher professionalism. The results of the implementation of activities to increase teacher professionalism carried out by the Principal of SMAN 2 Malang as a learning leader are assignment reports prepared by teachers, an increase in teacher performance, achievement of teacher achievement, student achievement and school achievement Keywords: improvement; teacher professionalism; learning leadership